2016
DOI: 10.1021/acs.jpca.6b07375
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanism of Bioactivation via S-Oxygenation of Anti-Tubercular Agent Ethionamide by Peracetic Acid

Abstract: The kinetics and mechanism of the oxidation of the important antitubercular agent, ethionamide, ETA (2-ethylthioisonicotinamide), by peracetic acid (PAA) have been studied. It is effectively a biphasic reaction with an initial rapid first phase of the reaction which is over in about 5 s and a second slower phase of the reaction which can run up to an hour. The first phase involves the addition of a single oxygen atom to ethionamide to form the S-oxide. The second phase involves further oxidation of the S-oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…5, the ability of losing electron was quantified and visualized on every site of amino acids by the calculated Fukui index (fk). The fk on sulfur atom in CYS and MET is much higher than that on the other sites, suggesting the strong affinity of sulfur-containing organics towards PAA oxidation, which is in accordance with the fact that most of the known organic compounds that react fast with PAA are those with sulfur atom(s) (Chipiso et al., 2016; Zhang et al., 2017). Moreover, the corresponding products are mostly sulfoxides and other following products.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…5, the ability of losing electron was quantified and visualized on every site of amino acids by the calculated Fukui index (fk). The fk on sulfur atom in CYS and MET is much higher than that on the other sites, suggesting the strong affinity of sulfur-containing organics towards PAA oxidation, which is in accordance with the fact that most of the known organic compounds that react fast with PAA are those with sulfur atom(s) (Chipiso et al., 2016; Zhang et al., 2017). Moreover, the corresponding products are mostly sulfoxides and other following products.…”
Section: Resultssupporting
confidence: 65%
“…The results in Table 3 indicate that LEU and THR may show less reactivity, while TRP could be a potential substrate for PAA oxidation due to its side chain indole. According to our work and published literature, compounds containing sulfur atoms or rings with nitrogen atoms are always found to be highly nucleophilic, and more likely to undergo PAA oxidation (Chipiso et al., 2016; Zhang et al., 2017). However, descriptorNk could only qualitatively predict the reactivities of amino acids, and more parameters and factors should be considered to establish a better model.…”
Section: Resultsmentioning
confidence: 55%
“…Several studies have investigated the possible oxidation of organic compounds by PAA and reported that PAA reactivity with respect to organic compounds is very selective. ,, ,, Overall, the oxidation mechanism of organic compounds by PAA is the transfer of a single oxygen atom from PAA to electron-rich sites on the compound. PAA reactivity is highly affected by the electron-withdrawing or electron-donating character of the substituents of organic compounds.…”
Section: Reactivity Of Organic Compounds With Respect To Paamentioning
confidence: 99%
“…However, despite the usage of PAA across several industries, research has been limited regarding the degradation of possible organic compounds in wastewater by PAA. To date, a few studies have investigated the oxidation of organic compounds by PAA, and they generally reported that the reactivity of PAA with respect to organic compounds is selective for specific structures. ,, So far, the reaction rate constants of PAA with many organic compounds remain unknown or undetermined, which significantly hinders a proper understanding of the fate of organic compounds and PAA in wastewater treatment processes.…”
Section: Introductionmentioning
confidence: 99%
“…ethionamide, which can be isolated. 42 Here, the sulphide carbon acts as a nucleophilic centre conjugated with the pyridinic nitrogen lone pair of electrons, which stabilize the electron density from the electrophile. Secondly, sulphur is easily oxidized at lower potentials because of the electronic hindrance due to its dense 3p orbitals.…”
Section: Mechanismmentioning
confidence: 99%